The Effect of Writing Prompts on Developing Argumentative Essays of Iranian University Students of English - Jalilifar, Alireza; Keyvan, Marjan; Don, Alexanne (Journal of Modern Languages, 2017)
This study aims to explore the effect of prompts as themes on developing argumentative essays that represent an important genre of academic writing. Thirty Iranian Master’s students of English Language Teaching and Literature took part in three consecutive test sessions arranged in this research. In each session, the students were divided into two groups: one provided with a writing prompt as a theme and the other without any prompts. The compositions were then rated and examined to find the possible effect of writing prompts on the students’ scores and the quality of their argumentative essays. At the same time, the relationship between the students’ scores and the organisation of the essays was checked based on a model of argument structure. The results revealed that writing prompts did not have any remarkable effect on the students’ scores and the quality of their argumentation. However, regarding the elements of the model, a strong positive relationship was detected between the scores and the frequency of occurrence of elements. Further research is needed to identify features which are likely to influence writing performance and improve argumentation.